1968
DOI: 10.20870/oeno-one.1968.2.3.1938
|View full text |Cite
|
Sign up to set email alerts
|

La cire cuticulaire des grains de raisin et des feuilles de la vigne

Abstract: Je voudrais parler ici des recherches que j'ai effectuées dans le cadre d'un programme de recherches de l'Organisation australienne de recherches (C.S.I.R.O.). Ce sont des recherches sur la structure, la composition chimique et le rôle de la cire cuticulaire des grains de raisins et des feuilles. Ces recherches ont été effectuées principalement lors de l'étude des problèmes relatifs au séchage des raisins pour la production des raisins. Cependant, l'importance de la cire cuticulaire ne se limite pas seulement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Works by Andreasen and Stier (1) and by Brechot (2,3) have demonstrated that certain sterols (ergosterol, lanosterol, and cholesterol) as well as oleanolic acid (which is an essential constituent of grape cuticle wax [14]) are yeast anaerobic growth factors.…”
mentioning
confidence: 99%
“…Works by Andreasen and Stier (1) and by Brechot (2,3) have demonstrated that certain sterols (ergosterol, lanosterol, and cholesterol) as well as oleanolic acid (which is an essential constituent of grape cuticle wax [14]) are yeast anaerobic growth factors.…”
mentioning
confidence: 99%